Advanced intermetallic Î³-TiAl based alloys with improved microstructural stability during creep. Issue 1760 (2nd January 2015) - Baker, I.; Heilmaier, M.; Kishida, K.; Mills, M.; Miura, S.; Kastenhuber, M.; Rashkova, B.; Clemens, H.; Mayer, S.
ABSTRACT Ensuring microstructural stability under technical relevant conditions is a determining criterion for the development of innovative high-temperature materials. In this work, the influ-ence of C and Si on the microstructural stability during creep exposure was investigated for a Î²-solidifying Î³-TiAl based alloy with a nominal composition of Ti-43.5Al-4Nb-1Mo-0.1B (in at.%), named TNM. With a two-step heat treatment a microstructure consisting of fine lamellar Î±2/Î³-colonies, surrounded by Î²o-phase and areas of discontinuous precipitation, starting from the boundaries of the lamellar colonies, was adjusted. Creep tests were carried out to examine the potential of C and Si to prevent microstructural instability during creep and hence improving the creep properties. At 815 Â°C the discontinuous precipitation process of the TNM alloy continues during ensuing creep testing leading to a reduced creep resistance. In comparison, the minimum creep rate of the TNM-0.3C-0.3Si alloy was significantly decreased caused by the lower Î²o-phase content and average lamellar spacing within the Î±2/Î³-colonies, the precipitation of p-Ti3AlC carbides and the retarded kinetics of discontinuous precipitation.